Unraveling the Multifaceted Nature of CD8 T Cell Exhaustion Provides the Molecular Basis for Therapeutic T Cell Reconstitution in Chronic Hepatitis B and C - Valeria Barili; Andrea Vecchi; Marzia Rossi; Ilaria Montali; Camilla Tiezzi; Amalia Penna; Diletta Laccabue; Gabriele Missale; Paola Fisicaro; Carolina Boni (Cells, 2021)
In chronic hepatitis B and C virus infections persistently elevated antigen levels drive CD8+ T cells toward a peculiar differentiation state known as T cell exhaustion, which poses crucial constraints to antiviral immunity. Available evidence indicates that T cell exhaustion is associated with a series of metabolic and signaling deregulations and with a very peculiar epigenetic status which all together lead to reduced effector functions. A clear mechanistic network explaining how intracellular metabolic derangements, transcriptional and signaling alterations so far described are interconnected in a comprehensive and unified view of the T cell exhaustion differentiation profile is still lacking. Addressing this issue is of key importance for the development of innovative strategies to boost host immunity in order to achieve viral clearance. This review will discuss the current knowledge in HBV and HCV infections, addressing how innate immunity, metabolic derangements, extensive stress responses and altered epigenetic programs may be targeted to restore functionality and responsiveness of virus-specific CD8 T cells in the context of chronic virus infections.